Towards Sustainable Mobility through a Change in Values. Evidence in 12 European Countries. - De-las-Heras-Rosas, Carlos Javier; Herrera-Ballesteros, Juan (MDPI, 2019)
The research carried out, as well as the measures taken to promote the use of sustainable transport in our cities, do not fully achieve their purpose. TheWertraitionalirat concept introduced by Max Weber in 1922 stated: “The use of public transport arises more from a system of values with which the person identifies than from the quality of the transport o ered”. This assertion made at the beginning of the 20th century is still valid, where the means, infrastructure and advances achieved do not obtain a proportional response from citizens. The aim of this work is, through this approach, to find variables that complement research on urban mobility habits. For this purpose, data from the International Social Survey Program (ISSP) and the European Social Survey (ESS) are used to analyse postmodern values and citizens’ environmental awareness, linking these to sustainable mobility habits in 12 European countries. The results suggest that a higher index of postmodern values implies greater environmental awareness, which would lead to a greater use of sustainable transport, although there are variables related to environmental knowledge and risk which indicate that greater environmental education and awareness is needed.
Keywords: Transporte sostenible - Países de la Unión Europea; Europe; Urban mobility; Postmodernism; Sustainable transport; Environmental awareness; Sustainability